UTILIZING ROSELLE IN FOOD PROCESSING: A STUDY ON NUTRITIONAL BENEFITS AND VALUE-ADDED PRODUCT DEVELOPMENT (International Journal of Food and Nutritional Sciences, 2022)
Roselle (Hibiscus sabdariffa L.), a tropical herbaceous plant, is valued for its vibrant calyces, which are used in beverages, jams, and jellies. Rich in antioxidants like gossypetin, hibiscetin, and sabdaretin, roselle also provides essential nutrients such as ascorbic acid, niacin, calcium, and iron. Despite its known medicinal and nutritional benefits, roselle remains underutilized in food processing industries. This study focuses on developing and standardizing technologies for processing and preserving roselle leaves, primarily through value addition in everyday culinary applications. One such approach is the preparation of a cooked vegetable dish (bhaji) using roselle leaves, which was evaluated for sensory attributes including appearance, aroma, texture, flavor, and overall acceptability. The leaves were sautéed with spices, including cumin seeds, garlic, turmeric, and chili powder, highlighting their potential as a savory component in diverse cuisines. A panel of 20 participants conducted a sensory evaluation of the dish, scoring it favorably across all parameters, particularly in appearance, aroma, and flavor. Additionally, the study investigated the nutritional content of roselle leaves, demonstrating their high protein, fiber, and carbohydrate content, making them a viable option for enhancing the nutritional value of meals. Furthermore, the preservation methods explored in this research offer insights into prolonging the shelf life of roselle leaves, enabling their use in both fresh and dried forms. This research provides a foundation for further exploration into the commercial potential of roselle in food processing, nutrition, and health, particularly in regions where it is traditionally grown but underutilized.